PERAN STRATEGIS CITY DIPLOMACY PEMERINTAH PALEMBANG DALAM MEWUJUDKAN KOTA BERKELANJUTAN RAMAH LINGKUNGAN - Sari Mutiara Aisyah; Nur Aslamiah Supli; Angelina Hosana Zefany Tarigan (Dauliyah Journal of Islamic and International Affairs, 2020)
This study was conducted to see the implementation of environmentally sustainable city development policies which are one of the pillars in the program of SDGs (Sustainable Development Goals) 2030 where local government is placed as the main actor. For the ASEAN regional level, the regional commitments of Regions for the development of environmentally sustainable cities are depicted in the ASEAN Socio-Culture Community Blueprint 2025. The review of this implementation aspect is aimed at identifying developments and challenges faced in the strategic policy of the Palembang City Government as the main implementing actor towards environmentally sustainable cities in the long term, with the Australia- Palembang Project-related the procurement of clean water and sanitation as a case study. In line with these objectives, this study uses qualitative research methods that are exploratory and descriptive in nature, where the depth and context of the data are important. This research results in the finding that the government of Palembang has been considered as an institution that has clear political objectives fully committed in the practice of city diplomacy to involve themselves directly even though it is limited to international cooperation through policy, and balanced communication between government agencies and AUS AID (as an international donor). The City Government is no longer seen as the object of implementing program plans formulated at the central level, but also has the opportunity to formulate a strategic plan or (bottom up) procedure based on the needs of local communities and the suitability of the model with environmentally sustainable city development.